ANALISIS PENGELOLAAN KEUANGAN PADA USAHA MIKRO KECIL DAN MENENGAH ( UMKM) DI KECAMATAN KUTOARJO - Caecilia Rosma Widiyohening; Riya Sapta Dewi (Politeknik Sawunggalih Aji, 2022)
Accounting is the main means to support a business implementation process. Many factors cause failure in small and medium micro businesses (UMKM. One of them is the low financial report. With financial statements the company can find out the condition of a company. Micro, Small and Medium Enterprises (UMKM) as a supporter of the nation's economy until now there are still many who have not applied accounting in running their businesses. This study aims to identify and analyze the application of accounting in Micro, Small and Medium Enterprises (UMKM) as well as constraints faced in them. The population in this study were MSMEs in Kutoarjo Sub-district engaged in trade and manufacturing. The method of taking research samples using random sampling which amounted to 93 respondents with an error rate of 10%. Data obtained through the results of questionnaires and documentation. The analysis technique of this study is qualitative descriptive. The results of this study indicate that of 93 respondents, (55.91%) UMKM in Kutoarjo District have recorded sales and (59.14%) records of purchases. For recording inventory (35.48%), costs (41.94%) and salaries only (23.66%). The obstacles that hampered UMKM in the application of accounting include UMKM assuming that making financial reports is too difficult. In addition, many UMKM do not understand and do not know how to make financial reports and there is no need for accounting applications.